2011
DOI: 10.3109/01443615.2011.625456
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of self-collected human papillomavirus specimens as a primary screen for cervical cancer

Abstract: The aim of this study was to compare the acceptability of self-collected vs clinician-collected human papillomavirus (HPV) tests. Utilising a cross-sectional approach, 250 non-pregnant, 25-60-year-old women from Leon, Nicaragua self-collected vaginal swabs and brushes for HPV and received a pelvic examination for liquid-based cytology and reflex HPV. Subjects underwent colposcopy, with biopsy if indicated, and completed questionnaires comparing their perceptions of HPV testing methods. Acceptability indices we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 22 publications
6
30
1
Order By: Relevance
“…This result demonstrates the feasibility of self-collection among Hopi women. As in other studies, most women reported positive attitudes toward self-sampling [6, 8, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40], with almost all reporting that the test was easy to use, and that they would recommend it to a friend or relative. A minority reported discomfort.…”
Section: Discussionsupporting
confidence: 72%
“…This result demonstrates the feasibility of self-collection among Hopi women. As in other studies, most women reported positive attitudes toward self-sampling [6, 8, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40], with almost all reporting that the test was easy to use, and that they would recommend it to a friend or relative. A minority reported discomfort.…”
Section: Discussionsupporting
confidence: 72%
“…One survey conducted in the US in 2013 estimated that 90 % of young adults aged 18-29 have a Facebook account, with 71 % identifying Facebook as their primary social media site [23]. To date, no HPV self-collection study has used online recruitment to recruit women to selfcollect a sample for HPV testing [22,[24][25][26][27]. The objective of this study was to determine the feasibility of initiating at-home HPV self-collected testing among women aged 21-30 in Minnesota who had been recruited using advertisements on the social networking site Facebook.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, findings from recent systematic reviews show that self-sampling was highly acceptable and that a majority of women preferred vaginal self-sampling to provider-collected cervical sampling [11,12]. As compared to the conventional speculum based Pap smear procedure, women preferred self-sampling because it was private, comfortable, less painful, and less embarrassing [13,14]. Moreover, research indicates that the correlation between self-collected and provider-collected samples was good [10,15].…”
Section: Introductionmentioning
confidence: 99%